Lord Apache - Steelman, Robert J. (Doubleday & Co. Garden City, N.Y., 1977)
Jack Drumm, a dandified Englishman making The Grand Tour, finds himself stranded with his valet in the middle of the Arizona desert. His struggle to survive against the savage elements and raiding Apaches becomes a struggle to conquer, to prove to the world that a civilized Englishman could overcome the savagery of the Western wilderness
46292
Keywords: Western; Apache Indians